The Feasibility of Social Science Learning E-Book Contains Balinese Local Wisdom for Elementary School - Dewi, Ni Kadek Rosita; Agung, Anak Agung Gede (Universitas Pendidikan Ganesha, 2021)
The results of the analysis of the needs for learning media in elementary schools show that teachers do not use innovative learning media during online learning and there is a lack of strengthening the values of local wisdom in the era of globalization. This study aims to develop an E-Book with the values of Balinese local wisdom. This type of research is a development research using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. Data collection used a questionnaire / questionnaire method with data analysis techniques, namely quantitative descriptive analysis. The results of E-Book media validation based on the expert's assessment of the content of social studies subject matter obtained a score of 87.50% with good qualifications, instructional design experts obtained a score of 100% with very good qualifications, learning media experts obtained a score of 92.50% with very good qualifications. The results of the individual user test on 3 students obtained a score of 93.33% with very good qualifications, and the results of the user test through a small group test on 12 students obtained a score of 94.16% with very good qualifications. Based on the results of product trial data analysis by experts and user subject test results, it is concluded that the E-Book media containing the values of Balinese local wisdom is suitable for use in learning social studies content in grade IV of Elementary Schools. The implication of developing this E-Book requires supporting facilities such as internet access, computers / laptops, cellphones and the ability of teachers or students to access E-Books.